The kidnapping in Tamaulipas and its consecuences - Arrona-Palacios, Arturo (Universidad Autónoma de Tamaulipas, 2011)
Tamaulipas is a state that is in a nationally important area, privileged with industrial and economic growth. This favors the incidence of kidnapping, considered a felony, as typifies our criminal procedure for attacking fundamental human value. At the national level it is a crime that must be stopped, using all means that the government has at its disposal. This study focuses on the analysis of the incidence of kidnapping in the state of Tamaulipas in the period between 2005- 2010. Information was obtained from the preliminary investigations undertaken in the Attorney General of the State of Tamaulipas and the Unit for Kidnapping Combat in the state. The kidnapping has a greater presence in the towns of Reynosa, Nuevo Laredo, Tampico and Matamoros, the predominant type of kidnapping in the state is the common type, followed by organized crime, in addition, males appear as the primary victim and the most common age range of 18 to 40 years. We conclude that in the state of Tamaulipas border cities have higher incidence of kidnapping in the years between 2005-2010.